2002
DOI: 10.1007/s00439-002-0781-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a natural variant of luteinizing hormone

Abstract: Luteinizing hormone (LH) plays an important role in the gametogenesis in both sexes by promoting the production of sex steroid hormones in the testes and ovaries. We previously described a genetic variant (V) of LH resulted from a mutation (G1502A) in the LH beta-subunit gene, causing the glycine102serine change in the protein hormone. This variant was subsequently found to be associated with both male and female infertility. In this study, we determined the functional aspect of this LH variant in vitro. Site-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Variant LH b is undetectable in a radioreceptor assay compared with the wild-type hormone [8] and it has lower receptor-binding activity [15]. Inactivating human LH b mutation results in absence or decreased number of Leydig cells [6] because LH is necessary for normal development of Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…Variant LH b is undetectable in a radioreceptor assay compared with the wild-type hormone [8] and it has lower receptor-binding activity [15]. Inactivating human LH b mutation results in absence or decreased number of Leydig cells [6] because LH is necessary for normal development of Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that hyposensitivity to FSH may be caused by an abnormal variant of the FSH receptor that reduces sensitivity to the receptor [70]. Mutations in the genes coding for LH [71-75] and the LH receptor [76-78] have been identified and these mutations may play a role in the cause of infertility, as well as influence the success or failure of fertility treatment. Further, it has been suggested that assessing serum androgen levels prior to initiation of COS may be beneficial for the selection of gonadotropin starting doses.…”
Section: Discussionmentioning
confidence: 99%
“…Both FGFR1 and PROKR2 were found to coincide with the same LHB variant (Gly122Ser) in 2 patients (Table 1 ). This LHB variant have been reported to significantly affect the binding ability of luteinizing hormone to its receptor and greatly reduce the biopotency for steroidogenesis of luteinizing hormone (Liao et al, 2002). No direct obvious correlation was observed between number of variants in oligogenic inheritance and spermatogenesis outcomes, partially because of relatively small number of patients.…”
Section: Oligogenic Patternmentioning
confidence: 96%